2021
DOI: 10.1111/dar.13314
|View full text |Cite
|
Sign up to set email alerts
|

Patients' beliefs towards contingency management: Target behaviours, incentives and the remote application of these interventions

Abstract: Introduction. Contingency management interventions are among the most efficacious psychosocial interventions in promoting abstinence from smoking, alcohol and substance use. The aim of this study was to assess the beliefs and objections towards contingency management among patients in UK-based drug and alcohol services to help understand barriers to uptake and support the development and implementation of these interventions. Methods. The Service User Survey of Incentives was developed and implemented among pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
(49 reference statements)
4
5
1
Order By: Relevance
“…The results are consistent with prior studies that support the use of technology to monitor behaviour and deliver incentives remotely [18–24]. Mobile telephone‐ownership has been reported to be as high as 96% among UK patients in treatment for substance use disorder, making mCM a feasible approach to address treatment‐related behaviour change [18].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The results are consistent with prior studies that support the use of technology to monitor behaviour and deliver incentives remotely [18–24]. Mobile telephone‐ownership has been reported to be as high as 96% among UK patients in treatment for substance use disorder, making mCM a feasible approach to address treatment‐related behaviour change [18].…”
Section: Discussionsupporting
confidence: 88%
“…The use of technology to monitor behaviour and deliver incentives remotely has been deemed appropriate and acceptable by patients surveyed in UK drug clinics, with 81% in favour of CM programs [18]. Engagement and compliance with remote behavioural monitoring procedures have been satisfactory, with many patients in receipt of mCM reporting the technology to be easy and straightforward to use [19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Investigations of client perspectives have found high acceptability of CM to clients receiving treatment for smoking, cocaine addiction, and alcohol consumption [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Recently, Getty et al [ 29 ] adapted provider questionnaires to produce the Service User Survey of Incentives (SUSI). London based service users (N = 181), most of whom had no prior experience of CM (92.3%), completed the SUSI.…”
Section: Introductionmentioning
confidence: 99%
“…Two systematic reviews have indicated that digital CM produces effects that are clinically meaningful and consistent with the results from in-person methods (Coughlin et al, in press; Getty et al, 2019). Patients also accept remote methods to monitor and incentivize drug abstinence (Getty et al, 2022). Furthermore, the COVID-19 global pandemic has catalyzed broad efforts to deliver remote therapy via smartphones and other modalities (Regnier & DeFulio, 2022; Sweeney et al, 2022).…”
Section: Technology To Promote Access To High-fidelity CMmentioning
confidence: 99%